Study of mechanical properties, microstructures and corrosion behavior of al 7075 t651 alloy with varying strain rate. Issue 1 (19th February 2015) - Mukherjee, A; Ghosh, M; Mondal, K; Venkitanarayanan, P; Moon, A P; Varshney, A
Abstract: Compression test of Al 7075 T651 was carried out at high strain rates (1138 – 2534 s −1 ) using Split Hopkinson Pressure Bar and at slow strain rate (10 −4 s −1 ) in 100KN Universal Testing machine to understand the improvement in mechanical properties and associated changes in microstructures. Cylindrical specimens of 6 mm height and 6 mm diameter were compressed dynamically. The influence of strain rates on mechanical properties, microstructure evolution and corrosion behavior after immersion test in 3.5% NaCl solution was also investigated. Strain rate, withdrawal stress and yield stress were observed to increase with impact velocity in high strain rate tests, while in slow strain rate tests, n value was observed to increase with increasing total strain. Microstructural observations revealed that after high strain rate test, grains of Al matrix were elongated. It was observed that corrosion resistance decreased with increase in impact velocity.